Nutrition in adolescents: physiology, metabolism, and nutritional needs. Issue 1 (April 2017) - Das, Jai K.; Salam, Rehana A.; Thornburg, Kent L.; Prentice, Andrew M.; Campisi, Susan; Lassi, Zohra S.; Koletzko, Berthold; Bhutta, Zulfiqar A.
Abstract : Adolescence is the period of development that begins at puberty and ends in early adulthood. Most commonly, adolescence is divided into three developmental periods: early adolescence (10–14 years of age), late adolescence (15–19 years of age), and young adulthood (20–24 years of age). Adolescence is marked by physical and sexual maturation, social and economic independence, development of identity, acquisition of skills needed to carry out adult relationships and roles, and the capacity for abstract reasoning. Adolescence is characterized by a rapid pace of growth that is second only to that of infancy. Nutrition and the adolescent transition are closely intertwined, since eating patterns and behaviors are influenced by many factors, including peer influences, parental modeling, food availability, food preferences, cost, convenience, personal and cultural beliefs, mass media, and body image. Here, we describe the physiology, metabolism, and nutritional requirements for adolescents and pregnant adolescents, as well as nutrition‐related behavior and current trends in adolescent nutrition. We conclude with thoughts on the implications for nutrition interventions and priority areas that would require further investigation.